Augmenting Sculpture with Immersive Sonification - Wang, Yichen; Gardner, Henry; Martin, Charles; Adcock, Matt (2022 IEEE Conference on Virtual Reality and 3D User Interfaces Abstracts and Workshops (VRW), 2022)
We present an artistic Mixed Reality (MR) system that remixes a sculptural element of a building and its aesthetic context to provide an on-site augmented art experience. Mainstream MR systems, particularly art-related, focus on the use of visuals in presenting additional information, whereas the use of audio as the main information channel has rarely been considered. In this work, we explore two different versions of a sonic experience for walking through an artistic staircase to enhance its public's engagement. Our user evaluation reveals the effectiveness of sonic design for a rewarding MR experience. With this, we emphasise the importance of sonic design in MR applications.